Merauke Regency KUA Strategy in Preventing Siri Marriage at an Early Age - Naufal Naufal; Hendra Yulia Rahman; M. Thohar Al Abza (The Indonesian Journal of Islamic Law and Civil Law, 2025)
Series marriages or marriages that are not registered at the Merauke Regency Religious Affairs Office have become a natural thing in today's society. Siri marriage is not only carried out for prospective couples of productive Age, but current series marriages are also carried out by prospective couples who are young/early (under the age of 19 years). Series or unrecorded marriages have a long-term adverse impact on those who do it. Therefore, cooperation between parties is needed to prevent serial marriages, especially young couples. Therefore, the KUA of Merauke Regency as an institution of the Ministry of Religion in each sub-district must prevent serial marriages from happening in Merauke Regency. So that this study will see what strategies or efforts have been made by the Merauke Regency KUA in preventing serial marriage for this early age couple. This research will be carried out through empirical studies with data collection using interviews, observations, and observations. The results of the study show that the rate of early marriage in Merauke Regency is quite large, from the early marriage there are 24 cases of itsbat nikah because the reason for the previous marriage was carried out by series marriage. With the findings of serial marriage at a young age, of course, the KUA of Merauke Regency has made various efforts and strategies to prevent serial marriage for prospective young couples, including assistance and assistance in the administrative process and optimization of Islamic religious extension workers in providing education, counseling, lectures, and community guidance related to the importance of marriage must be recorded.